Clinical heterogeneity in monogenic chylomicronaemia. Issue 11 (24th November 2022) - Heidemann, Britt E; Bemelmans, Remy H H; Marais, A David; Visseren, Frank L J; Koopal, Charlotte
Abstract : Chylomicronaemia accompanies hypertriglyceridaemia, usually due to a polygenic predisposition in combination with secondary risk factors. Monogenic chylomicronaemia represents a small subgroup of patients with hypertriglyceridaemia. This article describes three patients and illustrates the heterogeneity in the presentation of monogenic chylomicronaemia. The first case is a man with mild hypertriglyceridaemia who is a compound heterozygote for two variants in the LMF1 gene, without relevant medical history. The second case is a woman who is a double heterozygote of variants in the LPL and APOA5 genes. She experienced pancreatitis. The third case is a man, with recurrent pancreatitis attributed to severe hypertriglyceridaemia and homozygous for a variant in the APOC2 gene. This article highlights that in patients with hypertriglyceridaemia, the absence of pancreatitis or the presence of mild hypertriglyceridaemia does not exclude monogenic chylomicronaemia. Genetic screening should be considered in patients with unexplained or severe hypertriglyceridaemia, to determine appropriate treatment and follow-up.